Complete and prolonged response to anti-PD1 therapy in an ALK rearranged lung adenocarcinoma. (August 2020) - Baldacci, Simon; Grégoire, Valérie; Patrucco, Enrico; Chiarle, Roberto; Jamme, Philippe; Wasielewski, Eric; Descarpentries, Clotilde; Copin, Marie-Christine; Awad, Mark M; Cortot, Alexis B
Highlights: We report the first case of prolonged complete tumor response to immunotherapy in an ALK-rearranged NSCLC patient. This case supports the idea that some ALK rearranged NSCLC could durably benefit from immunotherapy. This case highlights the need for further studies to identify predictive factors of response to ICI in this population. Abstract: Objective: Immune checkpoint inhibitors (ICI) have become a major treatment in advanced non small cell lung cancer (NSCLC). However, some patients do not benefit from ICI, especially those harboring an ALK rearrangement. Here, we report a case of prolonged complete tumor response to immunotherapy in an ALK-rearranged NSCLC patient. Materials and Methods: We verify ALK expression and rearrangement on formalin-fixed paraffin-embedded tumor samples of the patient by Immunohistochemistry and Fluorescence In Situ Hybridization analysis. The patient provided written informed consent authorizing publication of clinical case. Results: We report the case of 48 years old man with a ALK-rearranged NSCLC. This patient displayed a complete response for 16 months under nivolumab therapy in third line setting after ceritinib and platin based chemotherapy. Conclusion: This is the first case of complete and prolonged response to ICI in ALK rearranged NSCLC. This case supports the idea that some ALK rearranged NSCLC could durably benefit from immunotherapy.